Role of Cox-2 in Vascular Inflammation: An Experimental Model of Metabolic Syndrome - Nicolás F. Renna; Emiliano R. Diez; Carina Lembo; Roberto M. Miatello (Mediators of Inflammation)
The objective of this work was to demonstrate the role of COX-2 enzyme at the vascular in experimental model of metabolic syndrome. SHR male WKY rats were employed; they were distributed in 8 groups (n=8 each): control (W); W + L: WKY rats receiving 20 mg/kg of lumiracoxib by intraesophageal administration; SHR; SHR + L: SHR + 20 mg/kg of lumiracoxib by intraesophageal administration; Fructose-Fed Rats (FFR): WKY rats receiving 10% (w/v) fructose solution in drinking water during all 12 weeks; FFR + L: FFR + 20 mg/kg of lumiracoxib by intraesophageal administration; Fructose-Fed Hypertensive Rats (FFHR): SHR receiving 10% (w/v) fructose solution in drinking water during all 12 weeks; and FFHR + L: FFHR + 20 mg/kg of lumiracoxib by intraesophageal administration. Metabolic variables, blood pressure, morphometric variables, and oxidative stress variables were evaluated; also MMP-2 and MMP-9 (collagenases), VCAM-1, and NF-κB by Westernblot or IFI were evaluated. FFHR presented all variables of metabolic syndrome; there was also an increase in oxidative stress variables; vascular remodeling and left ventricular hypertrophy were evidenced along with a significant increase in the expression of the mentioned proinflammatory molecules and increased activity and expression of collagenase. Lumiracoxib was able to reverse vascular remodeling changes and inflammation, demonstrating the involvement of COX-2 in the pathophysiology of vascular remodeling in this experimental model.